2005
DOI: 10.1189/jlb.0405190
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface expression of intermediate filament proteins vimentin and lamin B1 in human neutrophil spontaneous apoptosis

Abstract: Neutrophils represent an important source of autoantigens for antineutrophil cytoplasmic antibody associated with vasculitis. To date, two cytoskeletal proteins, vinculin and vimentin, have been reported to be expressed on the cell surfaces of activated macrophages, platelets, and apoptotic T lymphocytes. However, such cell surface expression has never been studied in human neutrophils. As we recently demonstrated that different cytoskeletal proteins were cleaved in apoptotic neutrophils, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
140
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 44 publications
8
140
2
Order By: Relevance
“…Intriguingly, a number of neo-epitopes are modified intracellular proteins that become exposed on the cell surface, as shown here with vimentin in the context of cellular senescence. The increased presence of MDA-modified vimentin on the surface of senescent cells may indeed serve as an "eat me" signal to immunocytes, as vimentin has been detected on the surface of apoptotic neutrophils (43,75) and T cells (76), which ultimately leads to phagocytosis by macrophages. Moreover, another study has suggested that cell-surface vimentin present on neighboring cells may interact with radiation induced O-GlcNAc-modified proteins from apoptotic cells to initiate their engulfment by macrophages (77).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, a number of neo-epitopes are modified intracellular proteins that become exposed on the cell surface, as shown here with vimentin in the context of cellular senescence. The increased presence of MDA-modified vimentin on the surface of senescent cells may indeed serve as an "eat me" signal to immunocytes, as vimentin has been detected on the surface of apoptotic neutrophils (43,75) and T cells (76), which ultimately leads to phagocytosis by macrophages. Moreover, another study has suggested that cell-surface vimentin present on neighboring cells may interact with radiation induced O-GlcNAc-modified proteins from apoptotic cells to initiate their engulfment by macrophages (77).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to playing a fundamental role as an intermediate filament in cytoskeletal assemblies, vimentin has been shown to associate with the nucleus and cell membranes of various cell types (37)(38)(39)(40)(41)(42)(43). Because 9H4 recognizes senescent cells by SACE analysis, which is an assay that requires robust antibody interactions with cell-surface antigens, we performed a cellular fractionation experiment to determine if vimentin was enriched on the surface of senescent NDFs.…”
Section: H4 Recognizes Vimentin and Oxidative Posttranslational Modimentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we demonstrated that among the different cytoskeletal proteins we have tested, paxillin, gelsolin, vinculin, a-and b-tubulin, only the IF protein vimentin and lamin B1 were expressed on the cell surface of apoptotic neutrophils, suggesting that neutrophils may be a source of autoantigens for the development of autoantibodies directed against vimentin and lamin B1 associated with various rheumatic diseases [17]. Furthermore, the presence of vimentin on the cell surface of apoptotic neutrophils may be involved in the recognition process of apoptotic neutrophils by phagocytes for the resolution of inflammation, although this remains to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Using the murine air pouch model, we have also demonstrated that vimentin was cleaved when neutrophils harvested from lipopolysaccharide (LPS)-induced air pouches were incubated in vitro with the potent pro-apoptotic plant lectin Viscum album agglutinin-I [18]. Given the importance of vimentin in general immunology [9,[19][20][21][22][23], inflammation and biology of neutrophils [10][11][12][13][14]17], and the fact that a generation of mice totally devoid of vimentin could develop and reproduce normally [3], we decided to investigate the role of vimentin during an inflammatory response in vivo and on neutrophil cell functions in vitro, two situations which have been curiously not or poorly investigated.…”
Section: Introductionmentioning
confidence: 99%